EXPLORING THE LINKAGE BETWEEN OIL AND GAS SECTOR AND COMPETITIVENESS: A PANEL DATA ANALYSIS FOR THE COUNTRIES OF THE BLACK SEA REGION - Ioannis ANTONIADIS (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2017)
The aim of this paper is to investigate the impact that oil and gas sector has on the global competitiveness of the economies of the countries of the Black Sea Region, measured by the Global Competitiveness Index, with the use of unbalanced panel data techniques for the period from 2006 to 2015. Factors concerning oil and gas sector as fuel exports, oil and gas prices, oil rents, and governance are used as independent variables. Both fixed and random effects models are estimated, and the validity of these models is assessed with the use of Hausman test. Our results are discussed and compared to relevant literature concerning other oil and gas producing regions.